Commitment and compliance : the role of non-binding norms in the international legal system - Shelton, Dinah (O.U.P OxfordGB, 2000)
Deals with three interrelated issues viz. the nature of international law; the role of legally non-binding norms or 'soft law' in the international system; and, compliance with international norms.